Calibration of Heat Source Models in Numerical Simulations of Welding Processes - Tomasz Kik (Metals)
This article presents issues related to the methodology of the correct definition of the heat source model in the numerical analyses of welding processes. The problem of determining the input data for the stage of a heat source model definition, obtaining input data from experiments, and their proper interpretation and use in defining the numerical model was discussed. Particular attention is paid to the specificity of the problem of defining the heat source model, the way of interpreting the results of the analyses and the way of comparing them with the results of real experiments. The basic problems related to the mapping of the complex geometry of the molten metal pool and the ways to solve them were indicated. The solutions and guidelines presented in the article allow to improve the accuracy and quality of the obtained results of numerical analyses, as well as to shorten the time of preparation of computational models by reducing the number of computational iterations related to the search for the maximum consistency of the compared values and temperature cycles.